2013
DOI: 10.1016/j.jcm.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of the impact sacroiliac joint manipulation has on walking kinematics using motion analysis technology

Abstract: Objective: The purpose of this study was to evaluate the feasibility of engaging in a series of larger studies measuring the effect of sacroiliac joint manipulation on walking kinematics using motion analysis technology. Methods: Twelve college students engaged in a baseline 90-second gait analysis at 1.5 mph using infrared VICON cameras. Following this, they underwent a prone heel comparison test for functional leg length inequality. Upon examination, participants were then classified as follows: left short l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…• No significant improvement seen in single-leg balance with eyes open in chiropractic group ( p = 0.43). Ward 2013 (USA) [ 162 ] RCT 11 (28.0) Healthy adults (18–45), college students, no CMT on the study day HVLA, superior ilium elongation Single manipulation No manipulation, participants with one short leg or no short legs Gait variability, f joint angles, DS time, stance time • No significant results to report. • Minor trends seen in the treatment group from baseline to study completion with an identified right short leg: increases in step length and stride length, decreases in right hip angle, and changes in double support time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…• No significant improvement seen in single-leg balance with eyes open in chiropractic group ( p = 0.43). Ward 2013 (USA) [ 162 ] RCT 11 (28.0) Healthy adults (18–45), college students, no CMT on the study day HVLA, superior ilium elongation Single manipulation No manipulation, participants with one short leg or no short legs Gait variability, f joint angles, DS time, stance time • No significant results to report. • Minor trends seen in the treatment group from baseline to study completion with an identified right short leg: increases in step length and stride length, decreases in right hip angle, and changes in double support time.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions employed within the scope of chiropractic practice were used in all 21 studies. The most commonly used interventions were SM (high-velocity low-amplitude (HVLA) or low-velocity mobilization) [ 34 , 46 , 114 , 158 – 160 , 162 170 , 173 ], soft tissue manipulation (myofascial release and stretching) [ 63 , 158 , 159 , 164 166 ], and thermal therapies (hot or cold packs) [ 63 , 158 , 159 , 165 , 166 ]. Two studies combined the chiropractic intervention with supervised rehabilitative exercises (SRE) [ 27 , 161 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations